Campus microenvironmental factors and their effects on people’s outdoor thermal perceptions under different conditions - Yang Zhang; Shuangyan Feng; Jiaying Liu; Quanzhang Mo; Hui Yin; Jian Zhang (Scientific Reports)
Abstract Pedestrians’ thermal perceptions can be adjusted by physical environmental factors. However, the thermal environments influenced by these factors are subject to current weather conditions. Subjective responses towards physical environments have rarely been investigated previously. This study explored microenvironmental factors and their impacts on thermal perceptions (evaluated by thermal sensation vote, TSV) on the campus of the Southwest University of Science and Technology (Mianyang, China). Through combining field measurement with questionnaire, it was found that neutral temperatures (NTs) of Mianyang during the measuring periods indicated by physiologically equivalent temperature (PET) were 28.41 °C (summer), 12.37 °C (winter), and 18.92 °C (the full year), respectively. Additionally, TSV linearly correlated with parameters of vegetation (indicated by the leaf area index, LAI), land surface reflectivity (albedo), and the water surface (distance from the lake, the distance for short). LAI was usually negatively correlated with TSV. The increase in LAI by 1 point contributed to the decrease of 0.171 in TSV (10:00, R2 = 0.295, p < 0.001, summer) and increasing the distance by 1 caused a rise of 0.076 in TSV (9:00, R2 = 0.367, p < 0.001, summer). Most importantly, the statistical significance of the models varied for contexts, especially weather conditions and daily time. Generally, the summer models (R2 = 0.391 maximumly) were more significant than winter (R2 = 0.263 at most), expressed by higher R2 values. In whole seasons, model R2 polynomial correlated with PET. The TSV showed the weakest correlation with microenvironmental parameters in the neutral temperature ranges. This study has revealed subjective responses towards physical environments under various context. The findings might be directive for future physical-environment design works in pedestrians’ thermal comfort improvements.